2017
DOI: 10.1080/07924259.2017.1398190
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth and morphological sexual maturity of the caridean shrimpNematopalaemon schmitti(Decapoda: Caridea: Palaemonidae) in an upwelling region in the Western Atlantic

Abstract: In crustaceans, successful reproductive processes, such as the transition from juvenile to adult, exhibit important morphological changes that can be detected by analyzing relative growth. This study describes the relative growth of body structures in Nematopalaemon schmitti and its secondary sexual characteristics, and also estimates the morphological sexual maturity of this species in a region influenced by upwelling. The carapace length (CL), second pleuron length (PlL), cheliped carpus length (CaL), chelip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…An increased slope of the adult stage, compared to the juvenile stage, for the CL versus AML relationship indicates the appendix masculina grows faster in the adult stage relative to the juvenile stage. Several studies (Ahamed & Ohtomi, 2014;Bauer, 2004;Herrera et al, 2017) also observed the transition or inflexion point in relative growth of the appendix masculine, proposing it could be used as an indicator of morphological sexual maturity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased slope of the adult stage, compared to the juvenile stage, for the CL versus AML relationship indicates the appendix masculina grows faster in the adult stage relative to the juvenile stage. Several studies (Ahamed & Ohtomi, 2014;Bauer, 2004;Herrera et al, 2017) also observed the transition or inflexion point in relative growth of the appendix masculine, proposing it could be used as an indicator of morphological sexual maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Crustacean growth is characterized by ontogenetic changes during their development, being widely used to observe and detect the transition point between the juvenile and adult stages (Dalabona et al, 2005;Hartnoll, 1978Hartnoll, , 1982Herrera et al, 2017;Vaninni & Gherardi, 1988;Wenner et al, 1974). Such studies of certain organs or body structures can be used to estimate morphological sexual maturity by differentiating between the juvenile and adult stages and the energy cost directed towards reproduction (Collins, 2001;Hartnoll, 1982;Taylor & Gabriel, 1992), along with the possible dimorphism between the sexes and between the juveniles and adults (Hartnoll, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovigerous condition (OF) was identified by the presence of eggs attached to pleopods. Shrimps with CL size equal to or greater than those estimated by Herrera et al (2018) for morphological sexual maturity were considered adults. According to this study, the established size for morphological sexual maturity was 8.5 mm for males and 9.3 mm for females.…”
Section: Sampling Of Specimens and Environmental Factorsmentioning
confidence: 99%
“…Shrimps are an important link between primary production and higher trophic levels (Kikuchi, 1966;Unsworth et al, 2007), and such information can assist in responsible planning for the conservation of species. Studies involving N. schmitti have been conducted in Brazil, including its ecological distribution (Almeida et al, 2012;Fransozo et al, 2009;Herrera et al, 2017), population structure (Almeida et al, 2011), fecundity and reproductive investment (Pereira et al, 2017) and relative growth and morphological sexual maturity (Herrera et al, 2018). Despite these studies, there is still a knowledge gap about assessing the reproductive parameters of species in a region with unusual features such as upwelling.…”
mentioning
confidence: 99%